Smart Solar Powered Charge Stations for Electric Vehicles - Erickson, Larry E.; Babcock, Michael; Boguski, Terrie; Brase, Gary L.; Griswold, Wendy; Kramer, Kimberly W.; Leven, Blase; Mirafzal, Behrooz; Natarajan, Bala; Pahwa, Anil (Kansas State University, 2012)
Smart solar powered charge stations (SSPCS) and smart microgrids that control power flow to electric vehicles at work sites, shopping malls, restaurants, schools, parks, etc. will become important as the number of electric vehicles (EVs) increases. Progress on the development of SSPCS will be presented. This will include the rationale for SSPCS and a triple bottom line analysis of SSPCS. Wide adoption of SSPCS will enhance and support the electrification of transportation and market penetration of EVs. Business models that include free parking and charging at SSPCS can be implemented to encourage people to electrify their transportation. Business models that include charge station control by power companies can include use of the power flow to the vehicles as a form of spinning reserve. Convenient and inexpensive charging of EVs is desirable and beneficial to all because significant electrification of transportation will impact gasoline supplies and prices over time.
Keywords: Solar; Photovoltaic; Shade; Sustainable; Convenient; Electric vehicles